Addressing the conundrum of unavailable name-bearing types - David L. Hawksworth (IMA Fungus)
Access to name-bearing type material can be a particular frustration for those mycologists in the tropics, or working outside established institutions, where the specimens are known to exist but cannot be examined. They can be inaccessible because of loans policies and the inability of mycologists to make personal visits. Each case has to be considered separately, but a pragmatic nine-point approach is presented which may provide some guidance as to what can be done in such instances. A postscript draws attention to 12 points to consider when designated or handling namebearing types.